2019
DOI: 10.1073/pnas.1906512116
|View full text |Cite
|
Sign up to set email alerts
|

Diverse repertoire of human adipocyte subtypes develops from transcriptionally distinct mesenchymal progenitor cells

Abstract: Single-cell sequencing technologies have revealed an unexpectedly broad repertoire of cells required to mediate complex functions in multicellular organisms. Despite the multiple roles of adipose tissue in maintaining systemic metabolic homeostasis, adipocytes are thought to be largely homogenous with only 2 major subtypes recognized in humans so far. Here we report the existence and characteristics of 4 distinct human adipocyte subtypes, and of their respective mesenchymal progenitors. The phenotypes of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
105
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 53 publications
3
105
1
Order By: Relevance
“…While lineage tracing cannot be performed in humans, relevant information can be derived from multipotent mesenchymal adipocyte progenitors present within adipose tissue. In previous studies, we observed that human adipocyte progenitor cells associated with the adipose tissue microvasculature differentiate into diverse functional subtypes 10 , 21 , and that the human thermogenic fat differentiation program is cell autonomous and depot-related 8 . In this paper, we leveraged these finding to investigate the gene expression signatures of progenitors and differentiated adipocytes from different human adipose tissue depots to define genes associated with the development of thermogenic adipocytes.…”
mentioning
confidence: 95%
“…While lineage tracing cannot be performed in humans, relevant information can be derived from multipotent mesenchymal adipocyte progenitors present within adipose tissue. In previous studies, we observed that human adipocyte progenitor cells associated with the adipose tissue microvasculature differentiate into diverse functional subtypes 10 , 21 , and that the human thermogenic fat differentiation program is cell autonomous and depot-related 8 . In this paper, we leveraged these finding to investigate the gene expression signatures of progenitors and differentiated adipocytes from different human adipose tissue depots to define genes associated with the development of thermogenic adipocytes.…”
mentioning
confidence: 95%
“…Human brown adipocytes differentiated in distinct adipose tissues express thermogenic genes at moderate levels under unstimulated conditions [2,14]. The ratio of brown and white adipocytes is partially determined during the early differentiation of mesenchymal progenitors into adipocyte subtypes, which is strongly influenced by genetic predisposition [19,20]. This can be quantified in a given tissue or cell culture sample by determining BATLAS score based on the expression of 98 brown and 21 white-specific genes, which were selected by a combined analysis of gene expression signatures in murine brown, beige, and white adipocytes and human tissue samples [21].…”
Section: Introductionmentioning
confidence: 99%
“…Human brown adipocytes differentiated in distinct adipose tissues express thermogenic genes at moderate levels under unstimulated conditions [2,14]. The ratio of brown and white adipocytes is partially determined during the early differentiation of mesenchymal progenitors into adipocyte subtypes which is strongly influenced by genetic predisposition [19,20]. This can be quantified in a given tissue or cell culture sample by determining BATLAS score based on the expression of 98 brown and 21 white-specific genes, which were selected by a combined analysis of gene expression signatures in mouse brown, beige and white adipocytes and human tissue samples [21].…”
Section: Introductionmentioning
confidence: 99%